Determination of high-frequency attenuation characteristic of coda waves in the central region of Nepal Himalaya (Journal of Nepal Geological Society, 2020)
The high-frequency coda wave attenuation in the central region of Nepal, in and around the Kathmandu valley, is estimated using vertical component seismograms of local earthquakes recorded at 16 different seismic stations of NAMASTE array. The estimated result is expressed in terms of Qc, quality factor (inverse of coda wave attenuation). The value of coda quality factor (Qc) is estimated at eight central frequencies of 1.5, 3.0, 6.0, 9.0, 12.0, 15.0, 18.0, and 21.0 Hz through four different coda window length from 20 to 50 s at 10 s interval by using the single backscattering model. The value of coda Qc obtained from this study, shows a clear dependence on a frequency according to the power relation, Qc (f)= Q0 f n, where Q0  is Qc  at 1 Hz, and f is frequency and n represents the degree of frequency dependence. The mean value of Qc of 16 different seismic stations was obtained as (110 ± 10.6) f 1.03±0.03 at 30 s coda window length, which represents the high attenuation characteristics of the study area, and attenuation decreases with increasing central frequency. Qo increases from 73.1 ± 10.1 to 156.1 ± 13.6 and n decreases from 1.12 ± 1.05 to 0.92±0.03 when the coda window length increases from 20 to 50 s. It is concluded that the study area is tectonically very active, highly heterogeneous, and heterogeneity decrease with depth. The coda Q obtained in this study is compatible with the result obtained in the region having a similar tectonic setting.